The sword motif "n Matthew 10:34 - Sim, David C. (Hervormde teologiese studies, 2000)
'n Mathew 10:34 Jesus uters a very dificult saying. He claims that he has not come to bring peace, but a sword. The form of this saying does not trace back to the historical Jesus; it is the product of Matthew's redaction of a Q passage which is found 'n a more original form 'n Luke 12:51. What did the evangelist mean when he wrote that Jesus brought a sword? 'n the Hebrew scriptures the sword was acommon symbol for the judgement and punishment of God, and 'n later times it represented a number of themes associated with the eschaton. It is argued 'n this study that Mathew, who was fully immersed 'n the apocalyptic-eschatological traditions of his day, probably used the sword motif 'n Matthew 10:34 to symbolise anumber of important eschatological events.